The effect of coconut shell as partially aggregate replacement toward concrete workability and strength - Muhammad Nasiruddin, Ahmad Yatim (2014)
Nowadays, the prices of building materials are rising day by day. The coarse aggregates are the main ingredients of concrete. Mainly, the selection of new materials in today's construction is due to resource constraint and cost-cutting measures thus, resulting in the selection of materials that do not have any value in the current market. By using these waste materials, concrete production cost can be reduced. This study presents the results of an investigation that was focus on laboratory test to determine the workability and compressive strength of the concrete using coconut shell as a concrete aggregate replacement. Concrete grade 30 was prepared and the coarse aggregate were replaced by 0%, 20%, 30%, 40%, 50% and 100% of coconut shell and were designated as Sample A, Sample B, Sample C, Sample D, Sample E and Sample F respectively. The objective of this study is to produce concrete by using waste material which is coconut shell. The size of coconut shell used is in the range of 10mm to 2 0mm. For the fresh concrete, slump test, vebe test and compaction factor test were conducted to determine the workability of the concrete. For hardened concrete, compressive strength test was conducted. 54 cubes with dimension 100mm x 100mm x 100mm have been prepared for this research. The specimens are tested at 7, 14 and 28 days. Type of curing used is water curing. The expected outcome from this research is the workability and strength of concrete will increase after using coconut shell as a partial aggregate replacement. The result obtain from this study shows that the increasing percentage of coconut shell replacement, make the workability of concrete which is medium workability for replacement at 0% to 50% while for 100%, workability become low. In term of compressive strength shows the same pattern as workability test. The compressive strength reduces as the coconut shell used in concrete.